2023
DOI: 10.1590/1806-908820230000011
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF pH ON THE ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF WOOD VINEGAR (PYROLIGNEOUS EXTRACT) FROM EUCALYPTUS

Abstract: The study aimed to assess the effect of progressive neutralization on the antimicrobial properties against bacteria and yeasts of wood vinegar obtained from the pyrolysis of Eucalyptus urograndis (clone I144) wood. Wood samples were carbonized at a heating rate of 0.9 °C min-1 until a final temperature of 450 °C, totalizing 8 hours of carbonization. The raw pyrolysis liquids were left to settle, and the aqueous fraction was separated. Then, the aqueous fraction (raw wood vinegar - WV) was purified to yield the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In Indonesia, WV from cocoa pod shells was found to act against fungal strains, including Candida albicans, with inhibition halos ranging from 6 to 6.12 mm [147]. Other studies have also reported the antifungal action of WV against C. albicans and other fungi [23,32,33,148].…”
Section: Wood Vinegar-an Effective Natural Antimicrobial Agentmentioning
confidence: 97%
See 2 more Smart Citations
“…In Indonesia, WV from cocoa pod shells was found to act against fungal strains, including Candida albicans, with inhibition halos ranging from 6 to 6.12 mm [147]. Other studies have also reported the antifungal action of WV against C. albicans and other fungi [23,32,33,148].…”
Section: Wood Vinegar-an Effective Natural Antimicrobial Agentmentioning
confidence: 97%
“…As mentioned above, phenolic compounds are recognized as responsible for WV's biological effects when used as an antimicrobial agent. Since at least 20 phenolic compounds are usually contained in WV, the probability of microorganisms simultaneously developing resistance mechanisms against all these substances is remote [33,142]. In addition to its antibacterial action, WV has high antifungal potential.…”
Section: Wood Vinegar-an Effective Natural Antimicrobial Agentmentioning
confidence: 99%
See 1 more Smart Citation